Transaxillary Approach for Thoracic Outlet Syndrome Case Report - Farasat Umar, Bilal Hassan Khan, Muhammad Zain Naseer, Haseeb Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
The brachial plexus and subclavian arteries are compressed when the thoracic outlet is expelled, resulting in the clinical disease known as Thoracic Outlet Syndrome (TOS). These disorders have various etiological causes, including cervical rib, and can damage the nervous system or blood vessels. The cervical rib, which develops from the seventh cervical vertebra and is thought to be abnormal, extra, or congenitally overdeveloped, is the main factor contributing to thoracic outlet syndrome (TOS). The transaxillary method developed by Roos, which is conservative and offers great exposure to the neurovascular structures with good aesthetic outcomes, is one of several surgical procedures employed for treating TOS. We present a case of a 43-year-old man with a cervical rib who complained of progressive pain and paresthesias in his left upper limb and presented to us in Ghurki Trust and Teaching Hospital Lahore . We removed the cervical rib and stented the Subclavian to the Brachial artery using a transaxillary approach. Keywords: Cervical Ribs, Transaxillary approach, Thoracic outlet syndrome